2021
DOI: 10.1073/pnas.2025121118
|View full text |Cite
|
Sign up to set email alerts
|

Ion-dependent protein–surface interactions from intrinsic solvent response

Abstract: The phyllosilicate mineral muscovite mica is widely used as a surface template for the patterning of macromolecules, yet a molecular understanding of its surface chemistry under varying solution conditions, required to predict and control the self-assembly of adsorbed species, is lacking. We utilize all-atom molecular dynamics simulations in conjunction with an electrostatic analysis based in local molecular field theory that affords a clean separation of long-range and short-range electrostatics. Using water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 64 publications
(87 reference statements)
0
21
0
Order By: Relevance
“…Electrostatic interactions are long-range forces ( 55 ), that follow the Coulomb’s law, whereby the potential bond energy varies inversely versus the distance between opposite charges. Hydrophobic interactions can occur between any residue depending on the increase in entropy gained by the removal of hydrophobic surface area from ordered solvating water.…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic interactions are long-range forces ( 55 ), that follow the Coulomb’s law, whereby the potential bond energy varies inversely versus the distance between opposite charges. Hydrophobic interactions can occur between any residue depending on the increase in entropy gained by the removal of hydrophobic surface area from ordered solvating water.…”
Section: Resultsmentioning
confidence: 99%
“…Except when heavy metals are present, most large-scale molecular simulations employ nonpolarizable force fields for computational efficiency, meaning that the only contributor to solvent polarization between semirigid bodies is the induced polarization of water molecules (although see ref for recent advances and applications of polarizable force fields in biology). This polarization is precisely measurable in simulations of modest length, and the far-field component of the polarization can be extracted by convoluting the resulting signal with a Gaussian of characteristic width as in local molecular field (LMF) theory . The boundary surface fields needed for Landau theory are therefore much more accessible than the surface potential needed for the Poisson–Boltzmann theory, which must be zeroed appropriately and is nontrivial to compute …”
Section: Methods For Computational Prediction Of Self-assembly Outcomesmentioning
confidence: 99%
“…472 Applying the Landau-LMF framework to the early stages of assembly of muscovite-binding proteins, Prelesnik et al found that the far-field polarization over muscovite mica changes dramatically when aqueous potassium was replaced with sodium. 294 This seemingly benign change to solution conditions resulted in mineral-protein interaction pressures of opposite signs, highlighting the importance of obtaining mean-field model parameters carefully. Such an effect is experimentally visible for proteins like C98 RhuA (see section 2.1.5), which binds to muscovite with one dipolar face or the other depending on the identity of the ions that pattern the surface.…”
Section: Solution Conditions and Mean Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we extend our previous work using all-atom molecular dynamics (MD) to interrogate the intrinsic response of the electrolyte solution at both mica–water and protein–water interfaces, now with specific focus on the physicochemical properties of two different, but closely related, types of mica. In that previous study, we were able to rigorously isolate the long-range polarization response between the front and back faces of two designed proteins in concentrated electrolyte solutions (3 M KCl and NaCl). Although these results provided a rationale for the observed specific ion effects that switch the binding face of these proteins, this long-range polarization was not a useful descriptor of the pronounced epitaxial alignment observed for lattices of both designed proteins.…”
mentioning
confidence: 99%